Time-Delayed Chaotic Dynamical Systems From Theory to Electronic Experiment - Banerjee, Tanmoy; Biswas, Debabrata; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book describes systematic design techniques for chaotic and hyperchaotic systems, the transition from one to the other, and their implementation in electronic circuits. It also discusses the collective phenomena manifested by these systems when connected by a physical coupling scheme. Readers will be introduced to collective behaviours, such as synchronization and oscillation suppression, and will learn how to implement nonlinear differential equations in electronic circuits. Further, the book shows how the choice of nonlinearity can lead to chaos and hyperchaos, even in a first-order time-delayed system. The occurrence of these phenomena, together with the efficiency of the design techniques described, is presented with theoretical studies, numerical characterization and experimental demonstrations with the corresponding electronic circuits, helping readers grasp the design aspects of dynamical systems as a whole in electronic circuits. The authors then discuss the usefulness of an active all-pass filter as the delay element, supported by their own experimental observations, as well as theoretical and numerical results. Including detailed analysis, as well as computations with suitable dedicated software packages, the book will be of interest to all academics and researchers who wish to expand their knowledge of the subtlety of nonlinear time-delayed systems. It also offers a valuable source of information for engineers, linking the design techniques of chaotic time-delayed systems with their collective phenomena.
I: Introduction -- II: First-Order Time-Delayed Chaotic and Hyperchaotic Systems: Design and Experiment -- III: Design and Characterization of Time-Delayed System with Bimodal Hard Saturation Type of Nonlinearity -- IV: Amplitude Death and Transitions Among Synchronized States in Mean-Field Coupled Time-Delayed System -- V: Synchronization in Hyperchaotic Time-Delay Electronic Oscillators Coupled Indirectly via a Common Environment -- A: Appendix. .
Keywords: Electronic circuits; Nonlinear Optics; Electric power production; Electronic Circuits and Systems; Nonlinear Optics; Electrical Power Engineering